Intranasal agomelatine solid lipid nanoparticles to enhance brain delivery: formulation, optimization and in vivo pharmacokinetics - Fatouh AM; Elshafeey AH; Abdelbary A (Dove Medical Press, 2017)
Ahmed M Fatouh,1 Ahmed H Elshafeey,1,2 Ahmed Abdelbary1 1Department of Pharmaceutics and Industrial Pharmacy, Faculty of Pharmacy, Cairo University, Cairo, Egypt; 2School of Pharmacy, University of Waterloo, Waterloo, ON, Canada Purpose: Agomelatine is a novel antidepressant drug suffering from an extensive first-pass metabolism leading to a diminished absolute bioavailability. The aim of the study is: first to enhance its absolute bioavailability, and second to increase its brain delivery.Methods: To achieve these aims, the nasal route was adopted to exploit first its avoidance of the hepatic first-pass metabolism to increase the absolute bioavailability, and second the direct nose-to-brain pathway to enhance the brain drug delivery. Solid lipid nanoparticles were selected as a drug delivery system to enhance agomelatine permeability across the blood–brain barrier and therefore its brain delivery.Results: The optimum solid lipid nanoparticles have a particle size of 167.70 nm ±0.42, zeta potential of -17.90 mV ±2.70, polydispersity index of 0.12±0.10, entrapment efficiency % of 91.25%±1.70%, the percentage released after 1 h of 35.40%±1.13% and the percentage released after 8 h of 80.87%±5.16%. The pharmacokinetic study of the optimized solid lipid nanoparticles revealed a significant increase in each of the plasma peak concentration, the AUC(0–360 min) and the absolute bioavailability compared to that of the oral suspension of Valdoxan® with the values of 759.00 ng/mL, 7,805.69 ng·min/mL and 44.44%, respectively. The optimized solid lipid nanoparticles gave a drug-targeting efficiency of 190.02, which revealed more successful brain targeting by the intranasal route compared with the intravenous route. The optimized solid lipid nanoparticles had a direct transport percentage of 47.37, which indicates a significant contribution of the direct nose-to-brain pathway in the brain drug delivery.Conclusion: The intranasal administration of agomelatine solid lipid nanoparticles has effectively enhanced both the absolute bioavailability and the brain delivery of agomelatine. Keywords: nasal route, direct nose-to-brain pathway, agomelatine